Media Development Learning Ladders Snakes Educative Subthemes Plants For First Grade Elementery School - Agustina, Winarti (UIN Fatmawati Sukarno Bengkulu, 2020)
Fun educational learning media rarely exist in the elementary school environment . So this study aims to develop educational learning media snake ladder with plant theme for firist grade elementery school. This research was conducted in three elementery schools in Bekasi. The method used is a research and development model with Borg & Gall. The results show aspects of media needs only 25% of teachers using games in learning media. While as many as 83% of teachers think the learning material in the book is very supportive theme to use instructional media. Researchers also conduct tests to students about the concept of living things, especially plants with an average value of 43.33 which enter into the category of